THE ANALYSIS STUDY OF MANAGEMENT OF CATARACT IN THE ADULT EYE: A CASE REPORT AND COMPREHENSIVE SYSTEMATIC REVIEW - Faisal Waber, Mahda (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Cataracts significantly impact vision, mental well-being, quality of life, and increase mortality rates and economic burdens. Age-related cataracts, the most prevalent form, gradually evolve over time due to cumulative cellular changes within the lens. The aim of this study is to evaluate the risk factors, management strategies, and prognosis in patients with senile cataract by analyzing a case report of a 73-year-old male patient with senile cataract and conducting a systematic review of literatures on the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Case Management: A 73-year-old male with controlled hypertension presented with worsening blurry vision, primarily in the left eye, diagnosed as immature senile cataract and presbyopia. Treatment includes lifestyle modifications and planned ECCE with phacoemulsification and IOL implantation, with a good prognosis. Result and Discussion: Initially retrieving 500 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. The literatures showed that age and hypertension in this case might be the contributing risk factors in senile cataract development. Conclusion: Cataract management requires a comprehensive understanding of risk factors, personalized treatment approaches, and evidence-based interventions. By addressing modifiable risk factors, adopting appropriate surgical techniques, and providing adequate patient education and support, clinicians can optimize outcomes and improve the overall quality of life for patients with senile cataracts.